We still have the symbols: study of the Treatises of Harmony of Antonio Colinas as an example of practical Philosophy (ALPHA. Journal of Arts, Literature and Philosophy, 2024)
I believe it is justified that, when referring to the "Treatises on Harmony" – T.A. from now on – by Colinas (2022), I do so with the understanding of a work possessing an internally observable unity, although its four texts were not written simultaneously. This is of minor importance. In addition to the editorial unity achieved by unifying the four treatises in the latest edition, the four "contemplations" (2010, p. 9), we notice an internal coherence in them, both due to the aphoristic genre and poetic prose in which they are written, as well as the thematic treatment. This latter aspect will be crucial as it brings us closer to the poet's more philosophical thought. Indeed, Colinas's modus operandi of writing is not a minor matter, as it allows us to inquire – although it is not the purpose of this article – into a philosophy that shuns all systems, writing more as if it were a flow of thoughts rather than constructing a building with logical and rational criteria.